Enhancing EFL students’ engagement through Canva talk up media in a pesantren-based school - Andina Silvi Amalia, Andina Silvi Amalia; Dwi Fita Heriyawati , Dwi Fita Heriyawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study was motivated by low levels of student engagement in English language learning within Pesantren-based (Islamic boarding school) educational settings, a context often characterized by conventional pedagogy and a scarcity of interactive instructional media. The research aimed to analyze the efficacy of Canva Talk Up media as a tool for enhancing engagement among English as a Foreign Language (EFL) students in this specific environment. Employing a qualitative descriptive design, the study involved one English teacher and four tenth-grade students at a Pesantren in East Java. Data were gathered through semi-structured interviews, non-participant classroom observations, and document analysis, and subsequently analyzed using thematic analysis. The findings indicate that the implementation of Canva Talk Up media significantly increased student engagement. This was facilitated by its visually compelling design, interactive features, and provision of an enjoyable platform for language practice. Concurrently, the teacher demonstrated enhanced proficiency in integrating technological, pedagogical, and content knowledge (TPACK). The study concludes that Canva Talk Up is an effective pedagogical tool for fostering student participation in this context, notwithstanding persistent challenges such as limited internet connectivity and device availability. The implications highlight the necessity for targeted teacher professional development and improved institutional investment in technological infrastructure to optimize the integration of digital learning media within Pesantren-based schools.